Multiple Thrombi in Portal Vein with Protein C and Protein S Deficiency: A Case Report - Rose Diana Kusumawati, Ninung; Juwita Pratiwi (Archives of Pediatric Gastroenterology, Hepatology, and Nutrition, 2025)
Background: Portal vein thrombosis (PVT) is a rare but significant cause of the gastrointestinal bleeding, often leading to delayed diagnosis due to its subtle presentation. PVT can result in portal hypertension, which cause the formation of portosystemic collaterals as a compensatory mechanism. Deficiencies in protein C and protein S are recognized as risk factor for PVT. This study aims to describe a rare underlying condition of PVT in children. Case: A 14-year-old boy presented with recurrent hematemesis and melena over the past eight years. Physical examination revealed no epigastric pain but showed splenomegaly. Laboratory findings showed pancytopenia, mildly elevated AST, prolonged plasma prothrombin time and partial thromboplastin time, increased INR, and low protein C and S. Endoscopic evaluation revealed esophageal and fundal varices, with portal hypertensive gastropathy. Multi-slice CT (MSCT) confirmed thrombosis in the main, right, and left portal veins, supporting the diagnosis of PVT. The patient was also diagnosed with an underlying myeloproliferative disorder, further contributing to his condition. Discussion: Protein C and S deficiency is a prominent risk factor of PVT. Identification of risk factors is essential to accurately treat the condition and prevent worse outcomes. Imaging modalities remain essential for diagnosing PVT. Management focuses on treating complication, particularly those related to portal hypertension, with endoscopic variceal ligation as the preferred treatment. Conclusion: Comprehensive investigation on etiology and risk factors, close monitoring and individualized treatment are essential in PVT management, especially in pediatric patients.